Hubungan Lama Perawatan dengan Outcome Tekanan Darah dan Proteinuria pada Preeklampsia Berat - Dwi Annisadillah; Fitri Rachmaini; Dian Ayu Juwita (Journal of Pharmaceutical and Sciences, 2025)
Severe preeclampsia is a major obstetric complication associated with maternal and perinatal morbidity and mortality. Hospitalization duration may influence clinical outcomes, including blood pressure and proteinuria, particularly in patients receiving antihypertensive therapy with nifedipine or methyldopa. This study aims to evaluate the association between the length of hospital stay and changes in systolic and diastolic blood pressure, as well as proteinuria, in patients with severe preeclampsia treated with nifedipine or methyldopa. This retrospective study reviewed medical records of patients diagnosed with severe preeclampsia and admitted to Dr. M. Djamil Central General Hospital, Padang, between January and December 2023. Patients were categorized into two groups based on hospitalization duration: <5 days and ≥5 days. All patients received monotherapy with either nifedipine or methyldopa. Data on patient demographics, clinical parameters, and hospitalization length were collected. Statistical analyses were performed using the independent t-test and the Mann–Whitney test, with a significance level of p<0.05. Of 60 patients included, 44 (73.3%) were hospitalized for ≥5 days, while 16 (26.7%) stayed <5 days. Patients with ≥5 days of hospitalization experienced a significantly greater reduction in systolic blood pressure (40.93 mmHg vs. 29.00 mmHg, p=0.025) and proteinuria (23.06 vs 33.20, p=0.031) compared to the <5-day group. No significant difference was observed in diastolic blood pressure reduction (p=0.128).